Beyond Charity:A Comparative Analysis on Waqfand Social-Based Healthcare Institutions in Malaysia - Nur Atika Atan; Rose Ruziana Samad; Fuadah Johari; Zurina Kefeli@ Zulkefli (USIM Press, 2024)
The Journal of Muamalat and Islamic Finance Research Volume: 21 No: 2 (page: 118-134)